Omvårdnadsrutiner för katt med astma - Wall, Marica (SLU/Dept. of Animal Environment and Health (until 231231), 2012)
Feline asthma is a condition very similar to the respiratory disease affecting humans. It is causing, among other things, a constriction of the bronchial airways, an increase of mucus production and damage to, or erosion of, the epithelial membrane. The symptoms occur intermittently and do, in most cases, evolve during a long period of time.